Strategi Pembelajaran Bahasa Arab untuk Generasi Z: Menggabungkan Media Sosial dan Metode Tradisional - Ahmad Purwanto (Multidisciplinary: Journal of Education an Learning, 2026)
This study aims to identify effective Arabic language learning strategies for Generation Z through a combination of traditional methods and the use of social media. The approach of this research is qualitative with literature studies, classroom observations, and semi-structured interviews with Arabic language educators. The results show that the integration of social media such as TikTok, Instagram, and other digital platforms can improve motivation, vocabulary mastery, speaking and writing skills, and student engagement when combined with the foundation of traditional methods such as formal grammar and oral exercises in physical classrooms. The research also shows challenges in the form of inequality of access to technology and the need for adequate training of educators. The implication of this study is the importance of a Blended Learning learning model that combines the power of face-to-face interaction and social media as a pedagogical tool to respond to the unique characteristics of Generation Z in Arabic language learning.